Highly Regioselective Allylic Substitution Reactions Catalyzed by an Air-Stable (π-Allyl)iridium Complex Derived from Dinaphthocyclooctatetraene and a Phosphoramidite Ligand - Ye, Ke-Yin; Zhao, Zhuo-An; Lai, Zeng-Wei; Dai, Li-Xin; You, Shu-Li (Synthesis, 2013)
An air-stable (π-allyl)iridium complex derived from dinaphthocyclooctatetraene and a phosphoramidite ligand has been synthesized and found to be highly efficient in iridium-catalyzed allylic substitution reactions. This catalyst features excellent regioselectivity and high stability. When NaCH(CO2Me)2 was used as the nucleophile, the catalyst loading in allylic alkylation reactions can be as low as 0.01 mol%.
Keywords: (π-allyl)iridium complex; allylic substitution; enantioselectivity; regioselectivity; dinaphthocyclooctatetraene